Low Vitamin D in psoriasis: Reality or myth? - Preethi B Nayak; Banavasi Shanmukha Girisha; Tonita Mariola Noronha; Handattu Sripathi (Indian Journal of Dermatology, 2018)
Context: Psoriasis is a chronic, systemic disease with the beneficial effect of topical vitamin D3 analogs, known for a long time. Low levels of vitamin D are increasingly found to be associated with the initial development of some autoimmune diseases. There are contradictory reports of low serum levels of vitamin D3 in the pathogenesis of psoriasis. Aims: (1) To determine the serum levels of vitamin D, calcium and C-reactive protein (CRP) in patients with psoriasis vulgaris, (2) To compare these levels with the serum levels of controls, and (3) To correlate them with the severity of the disease. Subjects and Methods: A hospital-based case–control study with 61 patients of psoriasis and 61 age- and sex-matched controls was undertaken. A detailed history was taken and examination including body mass index, Psoriasis Area and Severity Index (PASI) was done. Estimations of serum vitamin D, serum calcium, and CRP levels were done. Results: Mean 25(OH) vitamin D level was not significantly different between persons with and without psoriasis. Mean vitamin D level in cases was 18.41±9.41 and that in controls was 17.24±13.03 (P=0.63). However, vitamin D level were significantly lower in females than in males in both cases (P=0.02) and controls (P=0.006). There was no significant correlation between the severity of psoriasis and serum levels of vitamin D, serum calcium, and CRP. Conclusions: Serum level of vitamin D did not correlate with the severity of psoriasis in our study.